Health care seeking behavior of parents of under five in District Kanga, Himachal Pradesh - Minhas, Akshay; Chander, Vishav; Sharma, Seema; Bansal, P. (International Journal Of Community Medicine And Public Health, 2018)
Background: Health seeking behavior denotes the process involved in seeking a particular health state. Whereas, the healthcare seeking behavior of any individual denotes the end point contact of care. The objectives of the study were to understand the health seeking behavior and health care seeking behavior of parents of children, 0-5 yrs of age in Himachal Pradesh. Methods: A community based cross- sectional study on 2400 children of age less then and equal to 59 months was conducted. Morbidity profile and socio demographic indicators along with other variables were defined as indicators of health and health care seeking behaviour. The study was conducted using 30 cluster techniques with 80 participants from each cluster of district Kangra. Results: Water and sanitation was taken as one of the indicators of health seeking behavior and majority of our study population was dependent on ‘bavdi’ as water source. Earthen and steel pots were the most sought after storage vessel. In slums however plastic buckets were used. More than 80% of the households did nothing for purification. Majority responded that (82.6%) their child took bath daily. Institutional delivery was prevalent among 81.2% cases and lowest among rural slum. Nutrition was also taken as an indicator. Exclusive breast feeding was prevalent in 51.1% cases. In case of health care seeking behavior in our study around 47.0% parents visited the health facility, but also 24.0% were dependent on home remedies. Majority (30.5%), took treatment from secondary level of health care followed by 28.4% from private Ayurvedic Doctor. Conclusions: The system needs to understand its weaknesses as to why the population still practices unsatisfactory behavior across various areas. Especially in case of institutional deliveries, breast feeding and seeking treatment from a quack.